RETENSI KARYAWAN MEMEDIASI DAMPAK MANAJEMEN TALENTA TERHADAP KINERJA KARYAWAN (Studi Pada PD. BPR Djoko Tingkir Sragen) - Sugiyanto Sugiyanto; Sutianingsih Sutianingsih (JURNAL ILMIAH EDUNOMIKA, 2023)
The purpose of this research is to determine and analyze the effect of talent management on employee performance with employee retention mediating variables. The population as well as the sample are PD employees. BPR Djoko Tingkir Sragen. The research instrument uses a questionnaire. Data analysis with linear regression and path analysis and Sobel test. Conclusion: talent management and employee retention have a significant positive influence on employee performance. Talent management has a positive effect on employee retention. Employee retention mediates talent management against employee performance. Keywords : employee performance, employee retention, talent management.